Grasp posture modulates attentional prioritization of space near the hands - Thomas, Laura E. (Frontiers in Psychology, 2013)
Changes in visual processing near the hands may assist observers in evaluating items that are candidates for actions. If altered vision near the hands reflects adaptations linked to effective action production, then positioning the hands for different types of actions could lead to different visual biases. I examined the influence of hand posture on attentional prioritization to test this hypothesis. Participants placed one of their hands on a visual display and detected targets appearing either near or far from the hand. Replicating previous findings, detection near the hand was facilitated when participants positioned their hand on the display in a standard open palm posture affording a power grasp (Exp. 1, 3). However, when participants instead positioned their hand in a pincer grasp posture with the thumb and forefinger resting on the display, they were no faster to detect targets appearing near their hand than targets appearing away from their hand (Exp. 2, 3). These results demonstrate that changes in visual processing near the hands rely on the hands’ posture. Although hands positioned to afford power grasps facilitate rapid onset detection, a pincer grasp posture that affords more precise action does not.